Cross-cultural comparison of low back pain in the nursing workforce: A pilot study - Gilchrist, Andrea; Macková, Denisa; Pokorná, Andrea (International journal of nursing practice, 2024)
AIM: This study aimed to analyse cross-cultural differences in the prevalence of low back pain (LBP) and other back pain of general nurses in direct inpatient care in the Czech Republic (CZ) and Great Britain (GB). METHODS: The survey was used using an extended standardized Nordic Musculoskeletal Questionnaire and self-created additional questions. The data were analysed with Stata 15 using a significance level of 0.05. RESULTS: The data analysis was based on 1043 questionnaires. We identified statistically significant differences in the LBP prevalence between the respondents (CZ 93% and GB 85%) over a period of 12 months. Nurses in both countries stated a higher prevalence of LBP compared to pain in the neck, shoulders or upper back. LBP increases in relation to age, length of work experience, body mass index (BMI) and university education (BSc). Age, length of work experience, BMI and education (nursing college and master's degree) were confirmed as significant risks contributing to the increased prevalence of other back pain as well. Respondents reported a reduction in work performance, leisure activities and the need to change profession in relation to LBP. CONCLUSION: The results of the study confirm that LBP is a frequent occupational health issue in the general nurses working in direct inpatient care in both countries.
Keywords: dospělí; United Kingdom; průzkumy a dotazníky; Female; Prevalence; srovnání kultur; Adult; ženské pohlaví; Surveys and Questionnaires; lidé; Pilot Projects; Spojené království; Low Back Pain; pilotní projekty; prevalence; nemoci z povolání; Male; Czech Republic; lumbalgie; Cross-Cultural Comparison; Česká republika; Occupational Diseases; lidé středního věku; mužské pohlaví; Middle Aged; Humans